Research on the Application of Biochar in Carbon Sequestration: A Bibliometric Analysis - Shizhao Zhang; Shuzhi Wang; Jiayong Zhang; Bao Wang; Hui Wang; Liwei Liu; Chong Cao; Muyang Shi; Yuhan Liu (Energies)
Driven by global carbon neutrality goals, biochar has gained significant attention due to its stable carbon sequestration capabilities and environmental benefits. This research employs bibliometric tools such as VOSviewer 1.6.16, Citespace 6.2 R6, and Scimago Graphica to systematically analyze 2076 publications from the Web of Science Core Collection between 2007 and 2024, aiming to clarify the evolutionary trajectory, research hotspots, and international collaboration patterns of biochar carbon sequestration research while identifying future knowledge gaps for innovation. Research results reveal a three-stage developmental characteristic: 2007–2014 was a slow accumulation period for fundamental mechanism exploration, 2015–2020 was an accelerated expansion period driven by policies like the Paris Agreement, and 2021 to the present marks an exponential growth phase of interdisciplinary integration due to global carbon market consolidation. China and the United States are core producing countries, though inter-institutional deep collaboration remains insufficient. Research hotspots have progressively shifted from early biochar preparation and carbon stability to multiple waste materials (such as rice straw and urban carbon sequestration waste) and co-pyrolysis technologies (significantly emerging since 2022), with machine learning applications in process optimization becoming a nascent direction. The study recommends increasing cross-disciplinary research funding, establishing biochar raw material pollution standards, and promoting coordinated policies that combine biochar carbon sequestration with agricultural efficiency to support global carbon reduction objectives. Notably, the research’s reliance on the Web of Science Core Collection may limit coverage of non-English literature and regional studies. By quantitatively analyzing technological evolution and collaboration networks, this study provides a data-driven framework for optimizing biochar carbon sequestration strategies, helping bridge the gap between laboratory potential and actual climate emission reduction, and offering focused action pathways for policymakers and researchers.